KERALA FRESCO: - A STUDY OF TRADITION, DECLINE AND ITS REVIVAL - Todkar, Netra Ashish; Shirke, Mukta Avachat; Wagh, Vaishali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kerala mural painting is one of the breathtaking art forms of India. This art showcases Kerala’s artistic culture and also its spiritual heritage. Scenes from legends of Ramayana and Mahabharata, epics from Puranas and spiritual folklores are painted on the outer walls of the temple all over Kerala. These murals are rendered in only five colors derived from natural ingredients are the biggest collection of secco technique murals found in India. The art started around 9 century BC flourished during the Bhakti movement, peaked around 15th century CE and declined in early 19th century CE due to colonial influence and lack of institutional support. Although art schools and tourism have recently rekindled interest in Kerala murals, Commercial variations have lessened its styles authenticity. The paper discusses the origin, style characteristics and cultural importance along with the factors behind its decline and approaches required for reviving it. To make sure that this Legacy continuous and gets enriched in Modern Times the paper suggests strategies like inclusion in art education, state sponsored preservations, digital archives and involving community for its propagation. Through analyzing historical data visual observation and expert interviews these studies suggest how traditional arts may keep up the pace with current changing world